2021
DOI: 10.1001/jamanetworkopen.2021.16009
|View full text |Cite
|
Sign up to set email alerts
|

Cost Conversations About Anticoagulation Between Patients With Atrial Fibrillation and Their Clinicians

Abstract: IMPORTANCE How patients with atrial fibrillation (AF) and their clinicians consider cost in forming care plans remains unknown. OBJECTIVE To identify factors that inform conversations regarding costs of anticoagulants for treatment of AF between patients and clinicians and outcomes associated with these conversations. DESIGN, SETTING, AND PARTICIPANTS This cohort study of recorded encounters and participant surveys at 5 US medical centers (including academic, community, and safety-net centers) from the SDM4AFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Second, our study did not examine the quality of communication between patients and physicians, nor did it engage in content analysis to examine all aspects of cost conversations that could both enable and hinder adherence. A recent study by our group 12 found that cost conversations do in fact motivate patients to consider costs in choosing medications, although cost conversations did not impact the final choice of medication. Although our study found that cost conversations may not be associated with medication adherence, these previous findings point to the broad value of bringing costs to the attention of patients and, moreover, may guide clinicians to consider further aspects of cost conversations that might motivate better patient adherence.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Second, our study did not examine the quality of communication between patients and physicians, nor did it engage in content analysis to examine all aspects of cost conversations that could both enable and hinder adherence. A recent study by our group 12 found that cost conversations do in fact motivate patients to consider costs in choosing medications, although cost conversations did not impact the final choice of medication. Although our study found that cost conversations may not be associated with medication adherence, these previous findings point to the broad value of bringing costs to the attention of patients and, moreover, may guide clinicians to consider further aspects of cost conversations that might motivate better patient adherence.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, we have previously found that the clinical encounters supported by shared decision-making (SDM) tools that incorporate cost information increased the incidence of cost conversations compared with encounters not supported by SDM tools. 12 , 13 What is unclear is whether cost conversations with and without the use of SDM tools impact medication adherence.…”
mentioning
confidence: 99%
“…However, a recent study found that while such discussions were associated with patient consideration of treatment costs, they were not associated with choice of anticoagulant. 20 Given drug cost is associated with adherence, and adherence is associated with stroke risk, physician discussion of anticoagulation costs with patients is an important aspect of informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…By examining 830 audiovisual encounter recordings and participant surveys, the authors found that cost conversations occurred in a remarkably high 77% of all encounters and were more likely to occur when shared decision-making tools were used (90% vs 64% of encounters). 5 When examining physician factors associated with having cost conversations, the authors found that clinical load or years in practice did not matter but gender did. 5 Women doctors were more likely to have cost conversations, building on substantial evidence that, on average, they conduct longer visits with patients, engage in more shared decision-making, and have more patient-centered communication styles.…”
mentioning
confidence: 99%
“…5 When examining physician factors associated with having cost conversations, the authors found that clinical load or years in practice did not matter but gender did. 5 Women doctors were more likely to have cost conversations, building on substantial evidence that, on average, they conduct longer visits with patients, engage in more shared decision-making, and have more patient-centered communication styles. 6 These differences are likely attributable to a mix of differing patient expectations, sociocultural norms, and personal characteristics.…”
mentioning
confidence: 99%